Los estudiantes universitarios en la década de los setenta (2009)
ABSTRACT: Submerging in the reality of the society and the University gave by result the politicalization of the college students, understood as a taking of brings back to consciousness of the problematic general of the society in which the university is immersed. One said that the University, due to its academic task properly so and to its character of supplier of the tools of the social analysis, could not decide on any concrete alternative of change and yes it had to present/display them all The insertion of the studies of social sciences in the curriculum of the university schools technical scientists and experimental sciences in the field of the social human schools scientific, like imperative of the knowledge of the present reality and the culture, as also the impulse that occurred to the investigation in social sciences, that obtained quality, originality and creativity. This central direction of all the university task caused that the professional formation, without neglecting the academic thing projected towards the formation of professionals with high social sense, it jeopardize with the problematic improvement of the social one. Finally the University became, by virtue of this academic work, in a place of pluralistic encounter, where the most different positions were discussed and contrasted.